Bronchial gland duct ectasia in fatal bronchial asthma: association with interstitial emphysema. Issue 10 (October 1989) - Cluroe, A; Holloway, L; Thomson, K; Purdie, G; Beasley, R
Abstract : To determine the incidence of bronchial gland duct ectasia in fatal asthma and its association with interstitial emphysema, the histological features of 72 patients in whom death was considered to be due to asthma, and 72 matched control subjects in whom sudden death was not attributed to asthma, were reviewed. In all cases and controls, sections of two or more blocks of lung tissue stained with haematoxylin and eosin were obtained at necropsy. Bronchial gland duct ectasia was diagnosed if there was more than one abnormally dilated epithelial lined protrusion from a bronchus, extending through the smooth muscle layer. A histological diagnosis of asthma was made if four of the five following criteria were present: mucus plugging, basement membrane thickening, epithelial shedding, submucosal eosinophil leucocyte infiltration and smooth muscle hypertrophy. A histological diagnosis of asthma was made in 53 of 72 clinical cases of fatal asthma and in five of 72 control subjects. Interstitial emphysema was present in 10 clinical cases of fatal asthma, all of whom had bronchial gland duct ectasia and a histological diagnosis of asthma. Interstitial emphysema was not observed in control subjects. It is concluded that bronchial gland duct ectasia is a common histological feature of severe asthma, and that interstitial emphysema may be consequent on rupture of these dilated gland ducts.